Heavy Metal Tolerance of Bacterial Isolates from Solid Waste Dumping Sites in Abuja, Nigeria - Ojiego, Beatrice O.; Madu, Josephine; Ilo, Obianuju P.; Odoh, Joshua A.; Audu, Ephraim K.; Ishaku, Twan; Abdullahi, Shauibu A.; Gadzama, Ibrahim M.K.; Bolorunduro, Paul; Ella, Elijah; Ogu, Gideon I. (International Journal of Environment, 2023)
Bacteria have special bio-mechanism to resist toxic heavy metals. This study investigated heavy metal tolerance potentials of bacterial isolates from solid waste dumping sites (Abaji, Bwari, Gosa, Gwagwalada, Kuje, and Kwali) in Abuja, Nigeria. Soil samples were randomly collected from each location using soil augers at depths of 0 – 15, 15 – 35 and 35 – 45 cm. They were analyzed bacteriologically using cultural/biochemical techniques and chemically by exposing the isolates to graded concentrations (50 - 400 μg/mL) of chromium (Cr), nickel (Ni) and lead (Pb) on nutrient agar for heavy metal tolerance test. Statistical analysis revealed a significant decrease (p<0.05) in the heterotrophic bacterial count with soil depth; with the highest counts (6.89 × 109 CFU/g) noted at 0 – 15 cm (Gosa) and lowest (1.32 × 103 CFU/g) found at 30 – 45 cm (Kuje). The isolated bacteria (n=54) were Proteus (33.3 %), Providencia (29.6 %), Pseudomonas (16.6 %), Bacillus (9.3 %), Micrococcus (5.5 %), Escherichia coli (2.1 %), Enterobacter (2.1 %), and Serratia (2.1 %). All these isolates except Micrococcus spp., Enterobacter spp., Escherichia coli and Serratia spp. displayed 100 % resistance to Cr, Ni and Pb at ≥ 200 μg/mL with MICs (μg/mL) being 850 – 1700 (Pseudomonas – Proteus spp.), 950 – 2250 (Pseudomonas – Bacillus spp.) and 900 – 1750 (Pseudomonas – Bacillus spp.), respectively. Majority of these bacteria (24.1 - 38.9 %) were from Gosa and Gwagwalada dumping sites. Our findings suggested these bacteria could be promising for remediation of the heavy metals in the sites.